Organizational and institutional proximity effect on smes open innovation activities - Gyamfi, Solomon; Stejskal, Jan (Academic Conferences and Publishing International Limited, 2021)
Open innovation paradigm has become the anchor of the network economy in recent times. Due to the adoption of network systems as key developmental tools to create and share knowledge in an open system, a synergistic and network ecosystem has forced many firms to cooperate. Many such proponents of the collaborative ecosystem include the industrial district, innovative milieu and the proximity concepts that preceded Chesbrough’s open innovation concept. The underlying assumptions of these concepts lie in the fact that innovation is an interactive process, which is realized through a concerted effort of actors to create and share knowledge in a collaborative manner where the actors involved would reap the benefit and transcend the knowledge for the betterment of society. The open secret of SMEs is their inherent struggle to gauge and manage their collaborative sources of information auxiliary to their in-house innovation activities. However, looking at how knowledge is important, SMEs’ collaborative efforts must increase their institutional and organizational cooperation with other stakeholders within the industrial ecosystem. This will permit knowledge transfer between industrial players enabled by the interplay of institutional norms and mutual representation; likewise, SMEs are ensured syndicated transfer of tacit knowledge and access to diverse resources within their collaborative ecosystem. With this in mind, the paper using data from the CIS 2014 analyzed the effect of organizational and institutional proximity arrangement of SMEs in some selected CEE countries employing Partial Least Square Structural Equation Model for the empirical analysis. The results indicate that external and internal organizational and institutional proximity affect SMEs open innovation, although the findings show that the indirect effect of proximity on SMEs innovation performance through firms’ open innovation is stronger for only organizational proximity.
Vliv organizační a institucionální blízkosti na otevřené inovační aktivity malých a středních podniků
Keywords: collaboration; industrial district; innovation milieu; open innovation; proximity; spolupráce; industrial district; inovační prostředí; otevřená inovace; blízkost